Establishing the safety of waterbirth for mothers and babies: a cohort study with nested qualitative component: the protocol for the POOL study. Issue 1 (8th January 2021) - Milton, Rebecca; Sanders, Julia; Barlow, Christian; Brocklehurst, Peter; Cannings-John, Rebecca; Channon, Sue; Gale, Christopher; Holmes, Abigail; Hunter, Billie; Paranjothy, Shantini; Lugg-Widger, Fiona V; Milosevic, Sarah; et al.
Abstract : Introduction: Approximately 60 000 (9/100) infants are born into water annually in the UK and this is likely to increase. Case reports identified infants with water inhalation or sepsis following birth in water and there is a concern that women giving birth in water may sustain more complex perineal trauma. There have not been studies large enough to show whether waterbirth increases these poor outcomes. The POOL Study (ISRCTN13315580 ) plans to answer the question about the safety of waterbirths among women who are classified appropriate for midwifery-led intrapartum care. Methods and analysis: A cohort study with a nested qualitative component. Objectives will be answered using retrospective and prospective data captured in electronic National Health Service (NHS) maternity and neonatal systems. The qualitative component aims to explore factors influencing pool use and waterbirth; data will be gathered via discussion groups, interviews and case studies of maternity units. Ethics and dissemination: The protocol has been approved by NHS Wales Research Ethics Committee (18/WA/0291) the transfer of identifiable data has been approved by Health Research Authority Confidentiality Advisory Group (18CAG0153). Study findings and innovative methodology will be disseminated through peer-reviewed journals, conferences and events. Results will be of interest to the general public, clinical and policy stakeholders in the UK and will be disseminated accordingly.